Erratum: Characterization of a temperature-responsive two component regulatory system from the Antarctic archaeon, Methanococcoides burtonii (Scientific Reports (2016) 6 (24278) DOI:10.1038/srep24278) - Najnin, T; Siddiqui, KS; Taha; Elkaid, N; Kornfeld, G; Curmi, PMG; Cavicchioli, R (Scientific Reports, 2016)
Scientific Reports 6: Article number: 24278; published online: 07 April 2016; updated: 10 June 2016. This Article contains an error in Figure S3; where the labels ‘0 °C’ and ‘25 °C’ are inverted. The correct Figure S3 appears below as Figure 1.